Do probit models help in forecasting turning points in German business cycles? - Ulrich Fritsche (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
In this paper we used a data set constructed for a companion paper (Fritsche/Stephan, 2000) where we explored the leading indicator properties of different time series for the German business cycle. Now we test for the ability of different indicator series to forecast recessions by using a probit approach as proposed by Estrella/Mishkin (1997). The dating procedure refers to the study by Artis et. al. (1997). We took into consideration the criticism made by Dueker (1997) who stated that in the probit model the fact that the economy is already in a state of recession must be controlled for. The results of our estimate are unsatisfactory on the whole. Only the ifo institute's business expectation of producers of intermediate inputs, the interest rate spread, the long-term interest rate, and money supply M2 show satisfactory leading properties. – – In diesem Artikel wird ein Datensatz benutzt, mit dem auch in einer begleitenden Untersuchung die Frühindikatoreigenschaften verschiedener Reihen für den deutschen Konjunkturzyklus getestet wurden. Um die Fähigkeit, Rezessionen zu prognostizieren, zu testen, wird der von Estrella/Mishkin vorgeschlagene Ansatz benutzt. Für die Einteilung der Konjunkturphasen wurde auf Artis et. al. (1997) zurückgegriffen. Der Einwand von Dueker (1997), dass es wichtig ist, zu kontrollieren, ob die Wirtschaft sich schon in einer Rezession befindet, wurde berücksichtigt. Die Resultate der Schätzung sind insgesamt unbefriedigend. Nur die Ifo-Geschäftserwartungen von Vorleistungsgüterproduzenten, die Zinsdifferenz, die langfristigen Zinsen sowie die Geldmenge M2 zeigen befriedigende Vorlaufeigenschaften.
Keywords: 330; Konjunkturprognose; Prognoseverfahren; Konjunkturindikator; Probit-Modell; Schätzung; Deutschland